2021
DOI: 10.7759/cureus.13120
|View full text |Cite
|
Sign up to set email alerts
|

Ki67 Proliferation Index in Germinal and Non-Germinal Subtypes of Diffuse Large B-Cell Lymphoma

Abstract: Introduction Diffuse large B-cell lymphoma (DLBCL) is an aggressive B-cell lymphoma. The 2016 World Health Organization (WHO) update on hematopoietic tumors suggested that all DLBCL cases should be subtyped into germinal and non-germinal center phenotypes. Ki67 immunohistochemistry is a maker of cell proliferation and thus is used as a prognostic and predictive marker in various tumors of human body. Only a few studies evaluated the proliferative index of DLBCL subtypes in our population. Therefore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 21 publications
(9 reference statements)
0
6
1
Order By: Relevance
“…A daily examination of bone marrow involvement should be performed to adjust the treatment scheme. The Ki67 index of the non-GCB subtype is higher than that of the GCB subtype, which contradicted the results of this study [ 27 ]. Some studies showed a reverse relationship between the Ki67 index and clinical prognosis, while others did not [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A daily examination of bone marrow involvement should be performed to adjust the treatment scheme. The Ki67 index of the non-GCB subtype is higher than that of the GCB subtype, which contradicted the results of this study [ 27 ]. Some studies showed a reverse relationship between the Ki67 index and clinical prognosis, while others did not [ 28 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, it was claimed that the prognostic value of Ki-67 expression is limited and rather dependent on other patient features, such as bulk and IPI [ 14 ] or age [ 15 ]. It was also found that high Ki-67 expression is more common in non-germinal-center B-cell (non-GCB)-like DLBCL and is associated with c-MYC expression, which might partly explain the poorer outcome in those patients [ 16 ]. However, studies addressing Ki-67, IPI and treatment responses are not well established, as described in a systematic meta-analysis [ 4 ] which found that there is no clear relationship with IPI and that there are too few studies concerning treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Having the highest standardized canonical discriminant function coefficient value (1.024), MAIT population was the most impactful on the single discriminant function in Model 2 and, thus, on group separation. Group means did not significantly differ for the remaining four variables [CD38 + NK cells (NK cells with enhanced cytotoxicity and cytokine secretion 30 ) (en38NK), CD21 + CD27 − Ki67 + B cells (proliferating/activated naïve B cells 31 , 32 ) (actNB), CD27 + NK cells (NK cells with enhanced function 33 , 34 ) (en27NK), and CD27 − CD45RA + effector memory CD8 + T cells (terminally differentiated effector T cells 35 ) (Temra)]; these variables had relatively high Wilks’ λs (0.960, 0.852, 0.993, and 0.908, respectively), indicating that only small portions of their respective variances were related to group membership (Table 2 ). However, these variables were not useless to the model since incorporating each of them resulted in a highly significant boost to the discriminatory ability of the model—as indicated by the p -values associated with each step (see above and Table 1 )—and a decrease in the model’s Wilks’ λ (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%